قراءة تحليلية في واقع الصحة والسلامة المهنية في شركات الإسمنت - دراسة حالة شركة لافارج هولسيم – الأردن (Journal of Economics and Management Research, 2020)
تسعى الشركات اليوم إلى الحفاظ على سلامة العمال من المخاطر المهنية التي قد يتعرضون إليها، وهذا من خلال وضع نظام إدارة الصحة والسلامة المهنية لتوفير بيئة عمل آمنة من أي خطر يؤثر على العاملين من جهة وعلى أدائهم من جهة أخرى. وقد هدفت هذه الدراسة إلى تحليل وضع الصحة والسلامة المهنية بشركة لافارج هولسيم -الأردن وأولوياتها المستقبلية المتعلقة بهذا المجال، حيث أظهرت نتائج الدراسة أن الشركة وضعت خطط وبرامج وعقدت العديد من الدورات التدريبية بغية الوصول إلى صفر أذى في كافة مواقعها وهذا لتحسين مؤشرات الأداء المتعلقة بالصحة والسلامة المهنية. Companies today seek to preserve the safety of workers from the occupational hazards that they may be exposed to, and this by setting up an occupational health and safety management system to provide a safe work environment from any risk that affects workers on the one hand and their performance on the other hand. This study aimed to analyze the status of occupational health and safety in Lafarge Holcim - Jordan and its future priorities related to this field, as the results of the study showed that the company has developed plans, programs and held many training courses in order to reach zero harm in all its sites and this is to improve performance indicators related to health and safety Professional.